Analysis of Nutritional Value and Organoleptic Quality of Cookies Made From Sacha Inchi Nuts With A Combination Of Arrowroot Flour and Banana Flour As A Protein-Rich Food - Yusmiyati Yusmiyati; Rina Tri Lestari; Reni Lestari; Nur Sinta Dwi Prastiwi; Desi Dina Aulia (Rumah Sakit Akademik Universitas Gadjah Mada, 2026)
Background: Cookies are a staple food alternative with rich nutritional characteristics. Cookies have a delicious taste and crunchy texture. Objective: To produce cookie products with a combination of sacha inchi flour, banana flour and arrowroot flour that are high in protein, omega-3, 6, and 9 and high in fibre that can be accepted organoleptically.Method: Experimental research with a Completely Randomised Design (CRD). The treatment consisted of substituting sacha inchi flour with a combination of flours (banana, arrowroot, and wheat) to produce Formulas 01A, 02B, and 03C. With acomparison of sacha inchi nuts at 30% in formula 01A, 40% in formula 02B, and 50% in formula 03C. The nutritional values tested included water content, ash content, fat content, protein content, carbohydrate content, energy content, fibre content, total sugar content, and omega-3, 6, and 9 content. Organoleptic quality was tested using the Hedonic Test (preference test) with 30 consumer panellists who regularly consume cookies.Result: Based on the analysis of nutritional value (energy, fat, protein, carbohydrates, saturated fatty acids, unsaturated fatty acids, omega-3, 6, 9) and organoleptic quality, sacha inchi beans have the potential to be used at 50% in the formulation of cookies. That is, the cookies made with formula Sacha inchi cookie products, combined with arrowroot and banana flours, are an alternative source of protein with high nutritional value and omega-9 fatty acids, offering health benefits.